Membrane-forming composition and gas separation membrane
The film-forming composition uniformly disperses surface-modified fine particles in silicone by using a solvent with a specific dielectric constant, addressing aggregation issues and enabling high-quality gas separation membranes.
Patent Information
- Application Number
- JP2021561282
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-28
- Filing Date
- 2020-11-11
- Publication Date
- 2024-12-18
- Estimated Expiration
- 2040-11-11
AI Technical Summary
Conventional methods struggle to uniformly disperse surface-modified fine particles in silicone, leading to aggregation, sedimentation, and poor film flatness, especially in solvents that dissolve silicone, which limits the application to gas separation membranes with thicknesses of several 100 μm.
A film-forming composition is developed that includes surface-modified fine particles, a specific solvent with a dielectric constant of 1 to 30 containing oxygen or nitrogen atoms, and a solvent for dissolving silicone, ensuring uniform dispersion by optimizing the dielectric constant and solvent interaction.
The composition allows for the production of a silicone film with excellent dispersibility and film formability, enabling gas separation membranes without thickness restrictions.
Smart Images

Figure 0007602209000013 
Figure 0007602209000014 
Figure 0007602209000015
Abstract
Description
[Technical field]
[0001] The present invention relates to a membrane-forming composition, in particular a composition for forming a gas separation membrane, in which surface-modified fine particles are uniformly dispersed in a silicone and a silicone solvent. [Background technology]
[0002] Compositions in which fine particles are dispersed in silicone resins and films made from such compositions are used in a wide variety of applications, such as refractive index control materials, semiconductor encapsulation materials, and various separation materials. In order to maximize the properties of these materials, it is important that the fine particles are uniformly dispersed in the silicone resin, and various dispersion methods have been investigated. For example, methods of adding surfactants or leveling agents and methods of chemically modifying the surfaces of particles have been reported (Patent Document 1).
[0003] In particular, the inventors have found that chemical modification of the particle surface improves the dispersibility of the particles in various matrix resins (Patent Documents 2 and 3). On the other hand, it is known that fine particles with chemically modified surfaces do not have good dispersibility depending on the type of solvent, and are particularly poorly dispersible in solvents that silicone dissolves in. Therefore, even if attempts are made to disperse the surface-modified fine particles in silicone or a silicone solvent, aggregation or precipitation occurs, and as a result, there is a problem in that films prepared from these compositions have poor flatness. In addition, when particles whose surface has been modified with a polymer or the like are dried once as in Patent Document 4, it is not easy to redisperse them in silicone. In such cases, it is possible to disperse them using an appropriate dispersant and wet grinding, but this increases the number of steps in the dispersion process, and when silica fine particles are used, they are usually not completely disintegrated, leaving aggregates of fine particles, which limits the application to gas separation membranes with a thickness of several hundred μm. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-119848 A [Patent Document 2] WO2017 / 179738 publication [Patent Document 3] WO2018 / 038027 publication [Patent Document 4] JP 2012-224777 A Summary of the Invention [Problem to be solved by the invention]
[0005] As mentioned above, it is difficult to disperse surface-modified particles uniformly in silicone using conventional methods. It is possible to improve the dispersibility of these particles by using general dispersion methods (addition of surfactants, grinding, etc.), but when considering suitability for film production, there is a concern that the functionality of the originally designed particles may be impaired due to the adverse effect of additives on the resin performance, bleed-out, or residual aggregates of the particles.
[0006] In view of the above circumstances, the present invention aims to provide a film-forming composition capable of forming a silicone coating film having excellent flatness and particle dispersibility by thoroughly studying the components and mixing conditions for uniformly dispersing surface-modified microparticles in silicone and a solvent that dissolves silicone. The present inventors have focused on the relative dielectric constant of the solvent and found that when the relative dielectric constant of the solvent is within a specific range, the solubility of silicone and the solvent that dissolves silicone is good. Furthermore, they have found a film-forming composition that contains a specific solvent containing a heteroatom in order to provide an interaction between the surface-modified microparticles and the solvent. [Means for solving the problem]
[0007] That is, the present invention relates to a method for producing a gas separation membrane according to any one of the following first to eleventh aspects. First aspect: A film-forming composition comprising a silicone, a solvent capable of dissolving the silicone, surface-modified fine particles, and a specific solvent having one or more oxygen atoms or nitrogen atoms and a relative dielectric constant of 1 to 30. Second aspect: the film-forming composition according to the first aspect, wherein the specific solvent has a relative dielectric constant of 1 to 25. A third aspect: the film-forming composition according to the first aspect, wherein the specific solvent has a relative dielectric constant of 2 to 20. A fourth aspect: the film-forming composition according to any one of the first to third aspects, wherein the surface-modified fine particles are one or more kinds of fine particles selected from silica, zirconia, ceria, titania, alumina, and clay minerals. Fifth aspect: The film-forming composition according to the fourth aspect, wherein the surface-modified fine particles are silica. A sixth aspect: the film-forming composition according to the fifth aspect, wherein the surface-modified fine particles are silica having a dendrimer polymer or a hyperbranched polymer added thereto. Seventh aspect: The film-forming composition according to any one of the first to sixth aspects, wherein the specific solvent is one or more solvents selected from the group consisting of monohydric alcohols, monoesters, monoketones, and ethers. An eighth aspect: the film-forming composition according to any one of the first to seventh aspects, which is a composition for forming a gas separation membrane. A ninth aspect: a gas separation membrane formed using the membrane-forming composition according to any one of the first to eighth aspects. Tenth aspect: A semiconductor encapsulant formed using the film-forming composition according to any one of the first to eighth aspects. An eleventh aspect: a gas barrier material formed using the film-forming composition according to any one of the first to eighth aspects. Effect of the Invention
[0008] According to the present invention, a specific solvent having one or more oxygen atoms or nitrogen atoms and a relative dielectric constant of 1 to 30 is contained in silicone and a solvent for dissolving silicone, and the particles are mixed with a resin without being dried, thereby obtaining a film-forming composition in which surface-modified fine particles are uniformly dispersed. As a result, it is possible to provide a film with excellent film-forming properties in which the surface-modified fine particles are uniformly dispersed in the silicone film. In addition, since the dispersibility of the surface-modified fine particles is good, it is also possible to produce a gas separation membrane without any restrictions on the membrane thickness. [Brief description of the drawings]
[0009] [Figure 1] 1 is a SEM photograph of the surface of a film according to Example 13. [Diagram 2] 1 is a cross-sectional SEM photograph of a film according to Example 13. [Diagram 3] 1 is a SEM photograph of the surface of the film according to Comparative Example 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention will be described in detail below. The fine particles used in the present invention are nanoparticles with an average particle size of nano-order, and although the material is not particularly limited, inorganic fine particles are preferable. Here, the nanoparticles refer to those with an average primary particle size of 1 nm to 1000 nm, and particularly those with an average primary particle size of 2 nm to 500 nm. The average primary particle size is determined by the nitrogen adsorption method (BET method).
[0011] Examples of the fine particles include metal oxides such as silica, zirconia, ceria, titania and alumina, and clay minerals such as layered silicate compounds. Silica fine particles are preferred, and surface-modified silica fine particles are more preferred. In addition to spherical nanoparticles, the silica fine particles may also be irregularly shaped silica nanoparticles, such as elongated, beaded, or confetti-shaped silica nanoparticles, to provide a gas separation membrane with a significantly improved gas permeation rate. As the irregularly shaped silica nanoparticles, those described in International Publication WO2018-038027 may be used, and in particular, (1) elongated silica nanoparticles having a ratio D1 / D2 of the particle diameter D1 measured by dynamic light scattering to the particle diameter D2 measured by nitrogen gas adsorption, D1 being 40 to 500 nm, and having a uniform thickness within a range of 5 to 40 nm as observed by a transmission electron microscope, (2) spherical colloidal silica particles having a particle diameter D2 measured by nitrogen gas adsorption of 10 to 80 nm and silica bonding the spherical colloidal silica particles, and having a particle diameter D2 measured by dynamic light scattering of 10 to 80 nm, and having a particle diameter D2 measured by nitrogen gas adsorption of 10 to 5 ... Examples of the silica nanoparticles include (1) beaded silica nanoparticles in which spherical colloidal silica particles are linked together, in which the ratio D1 / D2 of D1 to the particle size D2 of spherical colloidal silica particles measured by a nitrogen gas adsorption method is 3 or more, and D1 is 40 to 500 nm, and (2) confetti-like silica nanoparticles having a plurality of wart-like protrusions on the surface of colloidal silica particles, in which the specific surface area S2 measured by the nitrogen gas adsorption method is S2 and the specific surface area S3 converted from the average particle size D3 measured by an image analysis method is S3, the surface roughness S2 / S3 value is in the range of 1.2 to 10, and the average particle size D3 is in the range of 10 to 60 nm. The irregularly shaped silica nanoparticles are more preferably surface-modified irregularly shaped silica nanoparticles.
[0012] The surface-modified silica is preferably one having a hydrophilic group introduced on the surface. The surface-modified silica having a hydrophilic group introduced on the surface can be obtained by treating a silane compound having a hydrophilic group with silica under heating conditions. The silane compound having a hydrophilic group can be, for example, aminopropyltriethoxysilane (APTES).
[0013] In addition, examples of surface-modified silica include silica nanoparticles in which a dendrimer polymer or a hyperbranched polymer is added to the silica surface. The following describes surface-modified silica nanoparticles of the dendrimer polymer or hyperbranched polymer-added type, with examples of the production method.
[0014] To produce surface-modified silica in which a dendrimer polymer or a hyperbranched polymer is added to the silica surface, the silica is first treated with a reactive functional group-containing compound having a functional group that reacts with a hyperbranch-forming monomer or a dendrimer-forming monomer while still dispersed in a first solvent, to obtain reactive functional group-modified nanosilica particles in which a reactive functional group is added to the silica surface. A preferred reactive functional group-containing compound is a silane coupling agent, for example, a compound containing an amino group at the end, represented by the general formula (1).
[0015] [ka] (In the formula, R1 represents a methyl group or an ethyl group, and R2 represents an alkylene group having 1 to 5 carbon atoms, which may have a substituent, an amido group, or an aminoalkylene group.)
[0016] In the silane coupling agent represented by the general formula (1), the amino group is preferably at a terminal, but does not have to be at a terminal. Examples of the compound represented by the general formula (1) include 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, etc. Representative examples of silane coupling agents having other amino groups include 3-ureidopropyltrimethoxysilane, 3-ureidopropyltriethoxysilane, 3-(2-aminoethylamino)propyltriethoxysilane, 3-(2-aminoethylamino)propyltrimethoxysilane, etc.
[0017] The reactive functional group-containing compound may also contain other groups, such as an isocyanate group, a mercapto group, a glycidyl group, a ureido group, or a halogen group, in addition to the amino group. Examples of silane coupling agents having a functional group other than an amino group include 3-isocyanatepropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-ureidopropyltriethoxysilane, and 3-chloropropyltrimethoxysilane.
[0018] The reactive functional group-containing compound used does not have to be a trialkoxysilane compound as represented by the general formula (1) above, and may be, for example, a dialkoxysilane compound or a monoalkoxysilane compound. The functional group of the reactive functional group-containing compound that reacts with the silanol group of the silica nanoparticles may be a group other than an alkoxy group, such as an isocyanate group, a mercapto group, a glycidyl group, a ureido group, or a halogen atom.
[0019] The treatment of silica nanoparticles with a reactive functional group-containing compound is carried out by adding the reactive functional group-containing compound to a liquid in which the silica nanoparticles are dispersed in water or an alcohol having 1 to 4 carbon atoms, and stirring the mixture. The reactive functional group can be added to the surface of silica nanoparticles by one-step reaction as described above, or can be added by two or more steps as necessary. A specific example of the two-step reaction is described in the preparation of carboxyl group-modified silica nanoparticles. For example, as described above, first, silica nanoparticles are treated with aminoalkyltrialkoxysilane to prepare amino group-modified silica nanoparticles, and then treated with dicarboxylic acid compound represented by general formula (2) or its acid anhydride to prepare silica nanoparticles in which the terminal of the reactive functional group added to the silica nanoparticles is a carboxyl group.
[0020] [ka] (In the formula, R3 represents an alkylene group having 1 to 20 carbon atoms which may have a substituent, or an aromatic group having 6 to 20 carbon atoms which may have a substituent.)
[0021] Examples of the compound represented by the above general formula (2) include malonic acid, adipic acid, terephthalic acid, etc. The dicarboxylic acid compound is not limited to those listed in the above formula. When reactive functional groups are added to the surface of silica nanoparticles in a reaction that exceeds two stages, a monomer having two amino groups at its terminal, represented by the following general formula (3), is added to silica nanoparticles that have been treated with the compound represented by formula (1) and then formula (2), thereby preparing silica nanoparticles in which the terminals of the surface modifying groups are amino groups, and the above reaction is repeated.
[0022] [ka] (In the formula, R4 is an alkylene group having 1 to 20 carbon atoms, or (C2H5-O-) p and / or (C3H7-O-) q wherein p and q each independently represent an integer of 1 or more.
[0023] Examples of the monomer represented by the general formula (3) include ethylenediamine, polyoxyethylenebisamine (molecular weight 2,000), o,o'-bis(2-aminopropyl)polypropylene glycol-block-polyethylene glycol (molecular weight 500), and the like.
[0024] The first solvent dispersion of the reactive functional group-modified silica nanoparticles thus prepared can be replaced with a second solvent to carry out the next reaction. The second solvent is a solvent more hydrophobic than the first solvent, and is preferably at least one selected from one or more of tetrahydrofuran (THF), N-methylpyrrolidone (NMP), dimethylaceroamide (DMAc), dimethylformamide (DMF) and γ-butyrolactone (GBL), or may be a mixed solvent.
[0025] The method of substitution with the second solvent is not particularly limited, and the wet precipitate obtained by concentrating the first solvent dispersion of reactive functional group-modified silica nanoparticles may be dispersed in the second solvent, or the first solvent may be distilled off without drying the first solvent dispersion of reactive functional group-modified silica nanoparticles, while the second solvent is charged to perform solvent substitution to obtain a dispersion in the second solvent.
[0026] After the solvent replacement, a dendrimer polymer or hyperbranched polymer having a multi-branched structure is added to the reactive functional group-modified silica nanoparticles in the presence of the second solvent using a second solvent dispersion of the reactive functional group-modified silica nanoparticles. That is, a dendrimer-forming monomer or hyperbranched polymer-forming monomer is reacted with the reactive functional group-modified silica nanoparticles to prepare silica nanoparticles having a dendrimer polymer or hyperbranched polymer added to the reactive functional group, thereby obtaining a second solvent dispersion of the dendrimer polymer- or hyperbranched polymer-added silica nanoparticles.
[0027] As the hyperbranched polymer forming monomer used in the present invention, it is preferable to use a compound having one carboxyl group and two amino groups represented by the following general formula (4), but it may also be a compound having three or more amino groups, and R5 may be a group other than an alkylene group having 1 to 20 carbon atoms and an aromatic group having 6 to 20 carbon atoms. Examples of the hyperbranched polymer forming monomer represented by the following general formula (4) include 3,5-diaminobenzoic acid and 3,5-diamino-4-methylbenzoic acid.
[0028] [ka] (In the formula, R5 represents an alkylene group having 1 to 20 carbon atoms which may have a substituent, or an aromatic group having 6 to 20 carbon atoms which may have a substituent.)
[0029] Furthermore, as the hyperbranched polymer-forming monomer, a compound having one carboxyl group and two halogen atoms, represented by the following general formula (5), can also be used.
[0030] [ka] (In the formula, R6 represents an alkylene group having 1 to 20 carbon atoms which may have a substituent or an aromatic group having 6 to 20 carbon atoms which may have a substituent, and X1 and X2 represent halogen atoms.)
[0031] Examples of the compound represented by the above general formula (5) include 3,5-dibromo-4-methylbenzoic acid, 3,5-dibromosalicylic acid, and 3,5-dibromo-4-hydroxybenzoic acid. Furthermore, the monomer for forming a hyperbranched polymer is not limited to the above-mentioned compound containing one carboxyl group and two or more amino groups, or one carboxyl group and two or more halogen atoms, but a monomer capable of forming a hyperbranched polymer can be used appropriately depending on the reactive functional group modified on the silica nanoparticles.
[0032] Furthermore, in the case of silica nanoparticles that have been surface-modified with carboxyl groups in a two-step reaction, hyperbranched polymers can be added using a compound having one amino group and two carboxyl groups, as represented by the following general formula (6).
[0033] [ka] (In the formula, R7 represents an alkylene group having 1 to 20 carbon atoms or an aromatic group having 6 to 20 carbon atoms which may have a substituent.)
[0034] Examples of the compound represented by the above general formula (6) include 2-aminoterephthalic acid, 4-aminoterephthalic acid, and DL-2-aminosuberic acid.
[0035] Furthermore, as shown in the following general formula (7), a monomer having one amino group and two or more halogens can also be used as a monomer for forming a hyperbranched polymer.
[0036] [ka] (In the formula, R8 represents an alkylene group having 1 to 20 carbon atoms which may have a substituent or an aromatic group having 6 to 20 carbon atoms which may have a substituent, and X1 and X2 represent halogen atoms.)
[0037] Examples of the compound represented by the above general formula (7) include 3,5-dibromo-4-methylaniline and 2,4-dibromo-6-nitroaniline.
[0038] When using silica nanoparticles that have been surface-modified with carboxyl groups in the above two-step reaction, the number of carboxyl groups and halogen atoms in the above general formulas (6) and (7) may be two or more, and other monomers having functional groups other than amino groups that react with carboxyl groups may be used, just as in the case of using silica nanoparticles that have been surface-modified with amino groups in the above one-step reaction.
[0039] The weight average molecular weight of a single chain of the hyperbranched polymer formed by these reactions is preferably, for example, about 200 to 2,000,000, and the branching degree is preferably about 0.5 to 1. The reaction can be carried out by dissolving the hyperbranched polymer forming monomer in one or more of the second solvents tetrahydrofuran (THF), N-methylpyrrolidone (NMP), dimethylaceroamide (DMAc), dimethylformamide (DMF) and γ-butyrolactone (GBL), adding and stirring the carboxylic acid activating reagent Benzotriazol-1-yloxytris(dimethylamino)phosphonium hexafluorophosphate (BOP) and the nucleophilic reagent triethylamine, and adding the amino group-modified silica nanoparticles to the solution and stirring. In addition to the combination of BOP and triethylamine, the carboxylic acid activating reagent may be triphenylphosphine, and the nucleophilic reagent may be pyridine.
[0040] Next, the silica nanoparticles to which a dendrimer polymer has been added will be described. First, the addition of a dendrimer to an amino group-modified silica nanoparticle will be described below. In the present invention, when a dendrimer is added to an amino group-modified silica nanoparticle, it is first necessary to add, for example, a monomer having three carboxyl groups represented by the following general formula (8) or a monomer having four or more carboxyl groups to the amino group-modified silica nanoparticle. Examples of the monomer that can be used include trimesic acid and pyromellitic acid.
[0041] [ka] (In the formula, R9 represents an alkylene group having 1 to 20 carbon atoms which may have a substituent, or an aromatic group having 6 to 20 carbon atoms which may have a substituent.)
[0042] Following the addition of the monomer having three carboxyl groups or the monomer having four or more carboxyl groups, a monomer having two amino groups at its terminal, represented by the following general formula (3), is added. By repeating these additions, dendrimer-modified silica nanoparticles are prepared.
[0043] [ka] (In the formula, R4 is an alkylene group having 1 to 20 carbon atoms, or (C2H5-O-) p and / or (C3H7-O-) q wherein p and q each independently represent an integer of 1 or more.
[0044] When silica nanoparticles modified with carboxyl groups as functional groups by the above-mentioned two-step reaction are used, the carboxyl group-modified silica nanoparticles are treated with a monomer having three amino groups represented by the following general formula (9), or a monomer having four or more amino groups. An example of a monomer having three amino groups is 1,2,5-pentanetriamine, and an example of a monomer having four or more amino groups is 1,2,4,5-benzenetetraamine.
[0045] [ka] (In the formula, R 10 represents an alkylene group having 1 to 20 carbon atoms which may have a substituent, or an aromatic group having 6 to 20 carbon atoms which may have a substituent.
[0046] Next, a monomer having two carboxyl groups at its terminal, represented by the following general formula (10), is added to the particles. Examples of the monomer include succinic acid, levulinic acid, and o,o'-bis[2-(succinylamino)ethyl]polyethylene glycol (molecular weight 2,000).
[0047] [ka] (In the formula, R 11 is an alkylene group having 1 to 20 carbon atoms, or (C2H5-O-) p and / or (C3H7-O-) q wherein p and q each independently represent an integer of 1 or more.
[0048] By repeating these additions, surface dendrimer-modified silica nanoparticles are prepared. Note that groups other than amino groups and carboxyl groups may also be used as the dendrimer-forming monomers.
[0049] The surface-modified silica nanoparticles to which the hyperbranched polymer or dendrimer polymer has been added thus prepared are mixed with a matrix resin to finally form a film. Note that the silica nanoparticles to which the hyperbranched polymer or dendrimer polymer has been added may be dried before being mixed with the matrix resin, or may be at least partially solvent-substituted with another second solvent or a solvent other than the second solvent.
[0050] In the present invention, silicone is used as a matrix resin. As such silicone, silicone resins generally used for film formation can be used. For example, commercially available silicones such as silicone YSR3022 and TSE382 manufactured by Momentive, KS-847T, KE44, KE45, KE441, and KE445 manufactured by Shin-Etsu Chemical Co., Ltd., and SH780 and SE5007 manufactured by Dow Corning Toray Co., Ltd. can be mentioned, but are not limited thereto. It is also possible to use silicone synthesized from a diorganopolysiloxane compound (monomer).More than one type of modified silicone or silicone as an antifoaming agent may be added to the silicone matrix resin.
[0051] Silicone can be used in combination with a crosslinking agent. Crosslinking agents are used to increase crosslink density or to improve heat resistance or durability. For example, when silicone with a hydroxyl group at the end is used, a silane compound having multiple hydrolyzable functional groups and its partial hydrolysis condensate can be used as the crosslinking agent. Specific examples of the silane compound include oxime silanes such as methyltris(diethylketoxime)silane, methyltris(methylethylketoxime)silane, vinyltris(methylethylketoxime)silane, and phenyltris(diethylketoxime)silane; alkoxy silanes such as methyltrimethoxysilane, methyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, phenyltrimethoxysilane, tetramethoxysilane, and tetraethoxysilane; acetoxy silanes such as methyltriacetoxysilane and ethyltriacetoxysilane; aminophenyltriethoxysilane-based silanes such as methyltris(dimethylamino)silane, methyltris(diethylamino)silane, methyltris(N-methylacetamido)silane, and vinyltris(N-ethylacetamido)silane; and aminoxy silanes such as methyltris(dimethylaminooxy)silane and methyltris(diethylaminooxy)silane. When a crosslinking agent is used in combination, the amount added is preferably about 0.1% by mass to about 20% by mass relative to the silicone.
[0052] The mass ratio of the silicone resin to the fine particles is, for example, 99 / 1 to 20 / 80, preferably 95 / 5 to 40 / 60, and more preferably 90 / 10 to 50 / 50.
[0053] The solvent for dissolving silicone is preferably a solvent with low polarity, and from the viewpoint of being difficult to evaporate naturally at room temperature during film formation, it is preferable that the boiling point is in the range of 60 to 200° C. For example, normal paraffin, isoparaffin, aromatic, and naphthenic solvents such as hexane, heptane, octane, isooctane, decane, cyclohexane, toluene, and xylene are included. Among these, decane and nonane are particularly preferable.
[0054] In addition to a solvent that dissolves silicone, the film-forming composition of the present invention contains, for the purpose of improving the dispersibility of fine particles, a solvent having one or more oxygen atoms or nitrogen atoms and a relative dielectric constant of 1 to 30. Here, the relative dielectric constant is the ratio of the dielectric constant of the solvent to the dielectric constant of a vacuum, and the relative dielectric constant of each solvent is described in the literature (National Bureau of Standards Circular 514, 1951).
[0055] The solvent that improves the dispersibility of the particles is a specific solvent having one or more oxygen atoms or nitrogen atoms and a relative dielectric constant of 1 to 30, preferably 1 to 25, more preferably 1 to 20. For example, preferred specific solvents include monohydric alcohols, monoethers, monoesters, and monoketones whose main chains are hydrocarbons, but are not limited thereto. Particularly specific examples include a single solvent or a mixed solvent of two or more of n-hexanol, n-heptanol, 4-heptanol, n-butanol, isopropanol, cyclohexanol, tetrahydrofuran (THF), propylene glycol monomethyl ether (PGME), and cyclopentanone.
[0056] The reason why a special solvent having one or more oxygen or nitrogen atoms and a relative dielectric constant of 1 to 30 improves the dispersibility of fine particles is not clear, but it is generally considered as follows. The first reason is that the special solvent used in the present invention is amphiphilic with a hydrophilic part and a hydrophobic part, and the particle surface has a hydrophilic part, so it is expected that the stabilizing effect of a general dispersant is caused. The second reason is that the silicone is adsorbed to the particle surface due to the terminal silanol group and siloxane bond site of the silicone, and the steric hindrance effect of the polymer is caused.
[0057] When n-hexanol is used as the specific solvent, the mass ratio of the silicone resin to the solvent is, for example, 1 / 99 to 50 / 50, preferably 1 / 99 to 30 / 70, and more preferably 2 / 98 to 10 / 90. The content of the specific solvent is set to be in the range of 0.01 to 70% by mass, preferably 0.1 to 50% by mass, and more preferably 0.1 to 30% by mass, based on the total solvent. In any case, the amount of the fine particles is set to be in the range of 0.01% by mass to 50% by mass, preferably 0.1% by mass to 15% by mass, based on the total mass of the film-forming composition.
[0058] In addition to the solvent that dissolves silicone, the film-forming composition of the present invention contains, for the purpose of improving the dispersibility of particles, a specific solvent having one or more oxygen atoms or nitrogen atoms and having a relative dielectric constant of 1 to 30. Therefore, it is preferable that the solvent that dissolves silicone and the specific solvent having one or more oxygen atoms or nitrogen atoms and having a relative dielectric constant of 1 to 30 are compatible with each other.
[0059] When a specific solvent having one or more oxygen atoms or nitrogen atoms and a relative dielectric constant of 1 to 30 can dissolve silicone, it can also be used as a solvent for dissolving silicone. In this case, the solvent contained in the film-forming composition of the present invention can be one type.
[0060] In the film forming composition of the present invention, the specific solvent is contained in addition to the silicone and the solvent that dissolves the silicone, and thus the dispersibility of the fine particles is significantly improved. The film-forming composition of the present invention can be easily dispersed in a good state by stirring means such as a mixer, but if necessary, it may be subjected to ultrasonic treatment, wet jet mill treatment, wet bead mill treatment, high-pressure homogenizer treatment, etc. This further improves the dispersion state.
[0061] For monohydric alcohols whose main chain is a hydrocarbon, the dispersion of the fine particles can be satisfactorily achieved by stirring alone and ultrasonic treatment is not required if the dielectric constant is within the range of 1 to 30. Also, for monoethers, monoesters, and monoketones whose main chain is a hydrocarbon, or other solvents, the dispersibility of the fine particles can be improved if the dielectric constant is within the range of 1 to 30. However, particularly in this case, when the dielectric constant is within the range of 1 to 10 or 18 to 30, it is preferable to carry out ultrasonic treatment after dispersion by stirring.
[0062] In the method for producing the film, the composition is applied onto a substrate, and then the solvent is evaporated. The substrate to be applied may be of any material or surface condition as long as it is not deteriorated by the solvent, and examples of the substrate include a Si wafer, a glass substrate, a PET film, and a PAN film without surface irregularities. Examples of nonwoven fabrics (supports) having pores on the surface include polyethersulfone (PES), polysulfone (PSF), polypropylene (PP), polyethylene (PE), polytetrafluoroethylene (PTFE), polyimide, polyamide, cellulose acetate, triacetate, polyacrylonitrile, and epoxy resin.
[0063] The coating method is preferably one that can coat the substrate uniformly and without unevenness, and known coating methods and coating techniques such as dip coating (immersion method), spin coating, blade coating, spray coating, bar coater method, microgravure method, gravure method, and slot die method can be used, but are not particularly limited. A blade coating method is preferred, and it is particularly preferred to use a doctor blade.
[0064] The present invention will be specifically described below by way of examples, but the present invention is not limited thereto in any way. EXAMPLES
[0065] The following examples will be described. The dielectric constants described in the examples are taken from the following documents: Reference 1 National Bureau of Standards Circular 514, 1951 Reference 2: Chemistry Handbook 2, Basics II, 5th Revised Edition, edited by the Chemical Society of Japan, Maruzen Publishing Co., Ltd., 621, 2014 Reference 3: JP 2015-191090 A
[0066] [Synthesis of surface-modified silica ST-G1] In a 1000mL four-necked round-bottom flask equipped with a cooling tube, a thermometer and a stirrer, 491.80g of silica isopropanol (IPA) dispersion (IPA-ST, Nissan Chemical Co., Ltd., silica concentration: 30.5% by mass, average primary particle size 12 nm), 2.69g of ultrapure water and 2494.5g of IPA were weighed out and heated to reflux while stirring. Then, 11.03g of APTES (Tokyo Chemical Industry Co., Ltd.) was added and stirred under reflux for 1 hour. The obtained dispersion was charged with 1-methyl-2-pyrrolidone (NMP) while distilling IPA and water with an evaporator, and the water content in the solution was confirmed to reach 0.1% by mass or less by a Karl Fischer moisture meter, and the process was terminated. Next, the APTES-modified silica concentration was adjusted to about 5.4% by mass with NMP. This solution was made into ST-G0-NMP sol.
[0067] The total amount of ST-G0-NMP sol obtained, 22.75 g of 1,3-diaminobenzoic acid (DABA) (manufactured by Aldrich), 15.13 g of triethylamine (TEA) (manufactured by Kanto Chemical Co., Ltd.), and 66.12 g of Benzotriazol-1-yloxytris(dimethylamino)phosphonium hexafluorophosphate (BOP) (manufactured by Tokyo Chemical Industry Co., Ltd.) were weighed into a 1000 mL four-neck round-bottom flask equipped with a condenser, a thermometer, and a stirrer, and the mixture was stirred at room temperature for 5 minutes, heated to 80 ° C, and reacted for 1 hour. After filtering this reaction liquid using filter paper (pore size 7 μm), the filtrate was poured into methanol in an amount 9 times the amount of the reaction liquid and allowed to settle. After that, the supernatant was discarded, and the same amount of methanol was added, and the mixture was stirred and allowed to settle. This operation was performed a total of 5 times, and washing was completed. This solution was designated as ST-G1-methanol sol.
[0068] [Preparation of ST-G1 / silicone dispersion] Momentive silicone YSR3022 and ST-G1-methanol sol were added to a recovery flask so that the mass ratio of silicone to ST-G1 was 9 / 1, and then toluene was added in an amount equivalent to the ST-G1-methanol sol and stirred. Next, the solvent was removed using an evaporator to an extent that the toluene was not completely removed, and then decane was charged to remove the remaining toluene. The final varnish concentration was adjusted to about 10% by mass. The varnish concentration here refers to the total solids concentration of silicone and ST-G1. This solution is also referred to as a silicone dispersion.
[0069] [Evaluation of varnish dispersibility] Example 1 The prepared silicone dispersion and n-hexanol (relative dielectric constant: 13.3, 25°C, Reference 1) as a specific solvent were dispensed into a screw bottle and diluted with decane to a varnish concentration of 5% by mass and n-hexanol of 10% by mass. The resulting dispersion was mixed in a mix rotor at 100 rpm for 1 hour, and then in a Thinky Corporation self-revolving mixer, Awatori Rentaro, at 2000 rpm for 3 minutes. After mixing, the screw bottle was left to stand, and the dispersion stability of the varnish after 3 hours was evaluated according to the following criteria.
[0070] [Evaluation Criteria] No visible sediment and sediment retention rate is 90% or more. Visible sediment and / or sediment retention rate < 90% × The sedimentation retention rate here is defined as follows. Sedimentation retention rate 100%: No sedimentation of fine particles observed Sedimentation retention rate 0%: Particles completely settled Sedimentation retention rate (%) = [Height of the top of the particle sedimentation layer from the bottom of the container / Height of the top of the varnish from the bottom of the container] x 100
[0071] Example 2 A varnish was prepared and evaluated under the same conditions as in Example 1, except that n-hexanol was replaced with n-heptanol (relative dielectric constant: 12.1, 22° C., Reference 1).
[0072] Example 3 A varnish was prepared and evaluated under the same conditions as in Example 1, except that n-hexanol was replaced with 4-heptanol (relative dielectric constant: 6.1, 22°C, Reference 1).
[0073] Example 4 A varnish was prepared and evaluated under the same conditions as in Example 1, except that n-hexanol was replaced with n-butanol (relative dielectric constant: 17.1, 25° C., Reference 1).
[0074] Example 5 A varnish was prepared and evaluated under the same conditions as in Example 1, except that n-hexanol was replaced with isopropanol (relative dielectric constant: 18.3, 25°C, Reference 1).
[0075] Example 6 A varnish was prepared and evaluated under the same conditions as in Example 1, except that n-hexanol was replaced with PGME (relative dielectric constant: 12.3, 20°C, Reference 3).
[0076] Example 7 A varnish was prepared and evaluated under the same conditions as in Example 1, except that n-hexanol was replaced with cyclopentanone (relative dielectric constant: 16.3, -51°C, Reference 1).
[0077] Example 8 A varnish was prepared and evaluated under the same conditions as in Example 1, except that n-hexanol was replaced with cyclohexanol (relative dielectric constant: 15.0, 25° C., Reference 1).
[0078] ( Comparative Example 9 ) The n-hexanol in Example 1 was changed to methyl ethyl ketone (MEK) (dielectric constant: 18.5, 20°C, Reference 1). In addition, regarding the dispersion method, a step of performing ultrasonic irradiation for 1 minute after the rotation-revolution mixer treatment was added. A varnish was prepared and evaluated under the same conditions as in Example 1.
[0079] ( Comparative Example 10 ) Comparative Example 9 The MEK was replaced with tetrahydrofuran (THF) (relative dielectric constant: 7.5, 22°C, Reference 2). Comparative Example 9 The varnish was prepared and evaluated under the same conditions.
[0080] ( Comparative Example 11 ) Comparative Example 9 Except for changing MEK to 1,4-dioxane (relative dielectric constant: 2.2, 25°C, reference 1) Comparative Example 9 The varnish was prepared and evaluated under the same conditions.
[0081] ( Comparative Example 12 ) Comparative Example 9 Except for changing MEK to ethyl acetate (relative dielectric constant: 6.0 at 25℃, Reference 1) Comparative Example 9 The varnish was prepared and evaluated under the same conditions.
[0082] Comparative Example 1 A varnish was prepared and evaluated under the same conditions as in Example 1, except that n-hexanol was not added.
[0083] Comparative Example 2 A varnish was prepared and evaluated under the same conditions as in Example 1, except that n-hexanol was changed to 1,2-hexanediol.
[0084] Comparative Example 3 A varnish was prepared and evaluated under the same conditions as in Example 1, except that n-hexanol was changed to propylene glycol.
[0085] Comparative Example 4 A varnish was prepared and evaluated under the same conditions as in Example 1, except that n-hexanol was changed to N-methylpyrrolidone (NMP).
[0086] Comparative Example 5 A varnish was prepared and evaluated under the same conditions as in Example 1, except that n-hexanol was changed to dimethylacetamide (DMAc).
[0087] Comparative Example 6 A varnish was prepared and evaluated under the same conditions as in Example 1, except that n-hexanol was changed to dimethyl sulfoxide (DMSO).
[0088] [Table 1]
[0089] From the above considerations, Examples 1 to 8. Comparative Examples 9 to 12 It was confirmed that this varnish had excellent dispersion stability compared to Comparative Examples 1 to 6.
[0090] [Evaluation of silicone film properties] (Example 13) The varnish concentration of Example 1 was changed to 2.5% by mass, and the mixture was mixed in a Mixer at 2000 rpm for 3 minutes, followed by 1 minute of ultrasonic irradiation. Next, a curing agent, YC6831 manufactured by Momentive, was added to the silicone at 7% by mass, and the mixture was mixed in a Mixer at 2000 rpm for 30 seconds to prepare a varnish. The resulting varnish was applied to a silicon substrate using a doctor blade (gap 50 μm), and then dried on a hot plate at 120° C. The surface condition and cross section of the resulting film were observed by SEM (FIGS. 1 and 2).
[0091] Comparative Example 7 The varnish used in Comparative Example 1 was modified so that the varnish concentration was 2.5 mass %, and the same coating and evaluation were carried out as in Example 13 (FIG. 3).
[0092] From the results of SEM observation, it was confirmed that the film of Example 13 was superior to that of Comparative Example 7 in terms of film flatness and particle dispersibility. The above results demonstrate that the varnish of the present invention is a composition that can provide a film having excellent particle dispersion stability, as well as excellent flatness and particle dispersibility.
Claims
1. The composition comprises: silicone; a solvent capable of dissolving the silicone; surface-modified silica; and a specific solvent having one or more oxygen atoms or nitrogen atoms and a relative dielectric constant of 1 to 30; the solvent for dissolving the silicone is at least one selected from normal paraffin, isoparaffin, aromatic solvents, and naphthenic solvents; the specific solvent is a single solvent or a mixed solvent of two or more solvents selected from the group consisting of monohydric alcohols consisting of n-hexanol, n-heptanol, 4-heptanol, n-butanol, isopropanol, and cyclohexanol, and the content of the specific solvent is 0.01 to 70 mass% of the total solvent; The surface-modified silica is selected from silica having a hydrophilic group introduced onto the surface of the silica, and silica having a dendrimer polymer or a hyperbranched polymer added onto the surface of the silica. Composition for film formation.
2. The film forming composition according to claim 1 , wherein the specific solvent has a relative dielectric constant of 1 to 25.
3. The film forming composition according to claim 1 , wherein the specific solvent has a relative dielectric constant of 2 to 20.
4. The film-forming composition according to claim 1 , wherein the surface-modified silica is silica to which a dendrimer polymer or a hyperbranched polymer has been added.
5. The film-forming composition according to claim 1 , which is a composition for forming a gas separation membrane.
6. A gas separation membrane formed using the membrane-forming composition according to claim 1 .
7. A semiconductor encapsulant formed using the film-forming composition according to claim 1 .
8. A gas barrier material formed using the film-forming composition according to claim 1 .
Citation Information
Patent Citations
Functional polysiloxane, preparation method of functional polysiloxane and application of functional polysiloxane in gas separation membrane
CN102827371A
Production of separation function composite hollow yarn body
JP1988171609A
Asymmetric gas separation membrane with outstanding gas separation capabilities
JP2010513021A
Room temperature curable organopolysiloxane composition and gas separation membrane
JP2012224777A
High separation efficiency silicone composite membrane
JP2013512100A
